2010
DOI: 10.1016/j.intimp.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle contractility assays for inflammatory and immunological mediators

Abstract: The blood vessels are one of the important target tissues for the mediators of inflammation and allergy; futher cytokines affect them in a number of ways. We review the use of the isolated blood vessel mounted in organ baths as important source of pharmacological information. While its use in the bioassay of vasoactive substances tends to be replaced with modern analytical techniques, contractility assays are effective to evaluate novel synthetic drugs, generating robust potency and selectivity data about agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…This result is consistent with other experiments demonstrating that inflammatory cytokines can influence ring tension. 13,14 Based on the results showing that vasorelaxation induced by gastrointestinal congestion plasma could be partially reversed by indomethacin, glibenclamide, BAY 11-7082, and SB 203580 and the results showing that hepatic artery rings treated with this plasma expressed higher levels of phospho-P38 MAPK protein and P38 MAPK mRNA, we concluded that the No, PgI 2 , the K ATP channel, NF-κB, and the P38 MAPK signal transduction pathway were involved in the vasorelaxation induced by this type of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with other experiments demonstrating that inflammatory cytokines can influence ring tension. 13,14 Based on the results showing that vasorelaxation induced by gastrointestinal congestion plasma could be partially reversed by indomethacin, glibenclamide, BAY 11-7082, and SB 203580 and the results showing that hepatic artery rings treated with this plasma expressed higher levels of phospho-P38 MAPK protein and P38 MAPK mRNA, we concluded that the No, PgI 2 , the K ATP channel, NF-κB, and the P38 MAPK signal transduction pathway were involved in the vasorelaxation induced by this type of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the umbilical vein rings was described elsewhere [20]. This vein is a suitable contractile bioassay for both the B 2 R and H 1 R [13,14]. After a 2.5-h equilibration period during which tissues were periodically washed with fresh Krebs buffer, tissues were randomly assigned to one of the experimental groups in several protocols further described in Results.…”
Section: Contractility Assaymentioning
confidence: 99%
“…Thus, the potency of L-alanyl-histamine as a contractile agent in the isolated vein (Fig. 5B) is determined by the enzymatic velocity of the APN, the diffusion rates of the pro-drug into, and that of the produced histamine out of the tissue and, possibly, by histamine degradation within the tissue (the general problem of non-equilibrium pharmacological effects on isolated tissues is discussed elsewhere [14]). …”
Section: Pharmacology and Metabolic Activation Of L-alanyl-histaminementioning
confidence: 99%
See 1 more Smart Citation
“…These and other isolated tissues are suitable to identify activating and inactivating pathways in the sense that local metabolism distorts the concentration-effect relationship of agonist peptides. Indeed, the concentration of these peptides at the vicinity of receptors in the smooth muscle is not necessarily in equilibrium with that present in the bathing fluid of the tissue, the rate of metabolic change caused by peptidases within the tissue being occasionally faster than the rate of agonist diffusion from the bathing fluid to the extracellular space of the tissue (this paradigm is illustrated with several examples relevant for peptide receptor ligands elsewhere [6]). We provide evidence for the paradoxical activation of Met-Lys-BK-Ser-Ser by ACE in vascular tissue.…”
Section: Introductionmentioning
confidence: 99%